2022
DOI: 10.1101/2022.04.19.488817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone methyltransferase Ezh2 coordinates mammalian axon regeneration via epigenetic regulation of key regenerative pathways

Abstract: SummaryCurrent clinical treatment for neurodegenerative diseases and neural injuries falls short of success, and one primary reason is that neurons in the mammalian central nervous system (CNS) lose their regeneration ability as they mature. Previous studies indicated that the regeneration ability of neurons is governed by complex signaling networks involving many genes. Therefore, here we investigated the roles of Ezh2, a histone methyltransferase, in regulation of mammalian axon regeneration at the epigeneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…As a result, the level of H3K27me3 was significantly increased after SNI. 50 Together, these data suggested that histone demethylases UTX and JMJD3 might function to suppress axon regeneration. To test this idea, we used our well-established in vivo electroporation technique 51 to co-transfect sensory neurons with a group of 4 different siRNAs against UTX or JMJD3 and the EGFP plasmid.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As a result, the level of H3K27me3 was significantly increased after SNI. 50 Together, these data suggested that histone demethylases UTX and JMJD3 might function to suppress axon regeneration. To test this idea, we used our well-established in vivo electroporation technique 51 to co-transfect sensory neurons with a group of 4 different siRNAs against UTX or JMJD3 and the EGFP plasmid.…”
Section: Resultsmentioning
confidence: 90%
“…As a result, the level of H3K27me3 was significantly increased after SNI. 50 Together, these data suggested that histone demethylases UTX and JMJD3 might function to suppress axon regeneration.…”
Section: Utx and Jmjd3 Are Negative Regulators Of Spontaneous Sensory...mentioning
confidence: 90%
“…Moreover, PTEN deletion-induced axon regeneration of mature RGCs was attenuated upon Tet1 KD. The histone methyltransferase Ezh2, a potential target of GSK3β ( Ma et al., 2013 ), was also documented to rejuvenate mature CNS neurons at the transcriptomic level by targeting H3K27me3, thus favoring axon regeneration ( Wang et al., 2022 ). However, to date, no direct evidence has shown that GSK3β acts upstream of these epigenetic modifiers to control axon regeneration.…”
Section: Gsk3 Signaling Regulates Neural Regeneration By Reshaping Th...mentioning
confidence: 99%
“…HATs and HDACs are characterized based on their cellular localization and substrate preference. All these major epigenetic modifications regulate optic nerve development [ 21 ] and recent studies have unraveled their important role in optic nerve protection, regeneration, and repair [ 22 , 23 , 24 , 25 ].…”
Section: Epigenetic Modifications Of Dnas and Histonesmentioning
confidence: 99%
“…Moreover, the study also showed inhibition of Ezh2 or G9a is associated with RGC death, thereby cementing the importance of histone methylation patterns in parts of the optic nerve. A recent study also showed that upregulation of Ezh2 is necessary for spontaneous axon regeneration of sensory neurons in different models [ 25 ]. Ezh2 does so by downregulating synaptic function-related genes, including Slc6a13 , which encodes GABA transporter 2.…”
Section: Epigenetics In Optic Nerve and Retinal Developmentmentioning
confidence: 99%